55.6: Research on the Bonding Technology of SUS And Panel for Curling Screen. (26th August 2021) - Mo, Wenwei; Ran, Chong
Abstract : In recent years, with the rapid development of display technology, flexible folding screen technology has become a must for major smart phone manufacturers to introduce new ones. With the continuous subversion of the industrial design concept of mobile phones, and the continuous optimization of product design and user experience, a new wave of mobile phone design has arrived‐curling screens. The curling screen is a new type of rollable and stretchable screen derived from the folding screen. The shrinkage and expansion of the screen is achieved through the Rolling component. The realization of the rollable screen relies on its rollable SUS as a support, and its curling characteristics directly lead to The difficulty of SUS fitting has increased dramatically. This article will study the technology of the SUS and Panel bonding (M‐Lami) of the curled screen, aiming to improve the bonding effect of the M‐Lami process and solve the difficult problems of the process: Peeling, tearing film reverse release, curved edge GDS. Through the tearing point of the tear film (right‐angle apex, right‐angle point up, right‐angle point down), curved edge roller bonding pressure (0.20MPa, 0.25MPa, 0.3MPa, 0.4MPa), roller diameter (11mm, 13mm, 15mm), 15mm), roller hardness (30IRHD, 40IRHD, 50IRHD) and other conditions are comprehensively researched and analyzed, and it is concluded that the tearing point of the film is 3mm above the right angle point, the curved edge roller bonding pressure is 0.3MPa, the roller diameter is 13mm, the roller Under the condition of hardness of 50IRHD, it can solve the problems of M‐Lami process Peeling, tearing film reverse release and curved edge GDS to the greatest extent, and improve the yield of curled screen products.